STRATEGI PENGENTASAN KEMISKINAN NELAYAN TRADISIONAL - Ismail Fahmi (PERSPEKTIF, 2016)
This study, on the activity of traditional fishermen difficult in economic Bagan Percut Village, District Percut Sei Tuan Deli Serdang regency. The method used in other research is qualitative methods, by conducting interviews, observation of Traditional Fishermen and chairman of the group of traditional fishermen as key informants.This paper provides an overview of the difficulty of the life of traditional fishermen and the harder it is economically driven, and after the study is expected to be seen clearly on the issue of economic hardship fishermen and strategies that can be taken by the government for poverty alleviation for the poor traditional fishermen.